2001
DOI: 10.1002/path.878
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor and brain-derived neurotrophic factor mRNAs are regulated in distinct cell populations of rat heart after ischaemia and reperfusion

Abstract: Neurotrophins play a crucial role in the development of the peripheral nervous system and their mRNAs are often regulated after several types of tissue injury. This study has investigated the regulation of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin-3 (NT-3) mRNAs 30 min after myocardial ischaemia followed by reperfusion, by northern blotting, and in situ hybridization in a rat model. Between 2 and 120 h of reperfusion, Ngf mRNA levels showed two- to four-fold up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 36 publications
10
80
0
Order By: Relevance
“…23 We found that statement of NGF and its trkA receptor is increased after induction of ischemia. Consistently, the system was found upregulated in models of cerebral or myocardial ischemia, 24,25 with NGF staining closely associated with capillaries, venules, and arterioles. 25 For the first time, here we document that upregulated NGF participates in reparative capillarization triggered by ischemic insult.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…23 We found that statement of NGF and its trkA receptor is increased after induction of ischemia. Consistently, the system was found upregulated in models of cerebral or myocardial ischemia, 24,25 with NGF staining closely associated with capillaries, venules, and arterioles. 25 For the first time, here we document that upregulated NGF participates in reparative capillarization triggered by ischemic insult.…”
Section: Discussionsupporting
confidence: 54%
“…Consistently, the system was found upregulated in models of cerebral or myocardial ischemia, 24,25 with NGF staining closely associated with capillaries, venules, and arterioles. 25 For the first time, here we document that upregulated NGF participates in reparative capillarization triggered by ischemic insult. In fact, spontaneous capillary growth was completely abrogated by anti-NGF antibody.…”
Section: Discussionsupporting
confidence: 54%
“…NGF is a potent growth and survival factor for sympathetic neurons (Korsching and Thoenen, 1985;Glebova and Ginty, 2004). Recent evidence indicates that NGF expression is up-regulated in the region of the infarction (Hiltunen, et al, 2001;Zhou, et al, 2004), and infusion of NGF into the stellate ganglion results in cardiac hyperinnervation in canine hearts (Cao, et al, 2000b). However, the cell types involved in post-infarct cardiac NGF production and the neural selectivity of the response are not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…1). In animal heart, BDNF expression was found to be upregulated after ischemia-reperfusion injury in the left ventricle (20), suggesting both neuronal and non-neuronal functions for neurotrophins in …”
Section: Bdnf Blood Level and Its Associatesmentioning
confidence: 99%